(untitled) (Bangladesh Journal of Medical Science, 2016)
Objective: research is to study the role of L-carnitine, tumor necrosis factor ? (TNF-?), and interleucine-6 (IL-6) in the development of NASH. Materials and Methods: examined 65 patients with NASH. Blood serum L-carnitine, TNF-? and IL-6 level was estimated using the enzyme-linked immunoassay method. Results: patients with NASH had a decreased blood serum level of L-carnitine. L-carnitine level was found to be in strong inverse correlation dependence on cellular damage markers, L-carnitine levels affect the performance TNF-? and IL-6. Conclusion: L-carnitine contributes to lipotoxic stress development and development of systemic liver inflammation. Bangladesh Journal of Medical Science Vol.15(1) 2016 p.62-65